Pengembangan Sistem Pengelolaan Pemasukan dan Pengeluaran Keuangan Berbasis Web - Amirul Iqbal (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
The advancement of information technology especially in computerized systems is snowballing. It is also backed by a range of demands from industry/ companies that want to abandon the conventional way of conducting business operations to the use of information technology. MÈMORE is a company engaged in the decoration and crafts industry. The company is now using a computerized system in the form of Microsoft Excel software to monitor the company's income and expense and the company often maintains a separate report in a special book. However, this causes problems for these businesses as there is no more efficient method for data processing or for handling the income and expense. In order to solve the problems of the company, a computerized system of financial management is required that will be tailored to the problems and needs of the owner of the business in order to support the company's growth with reliable, managed, and safe financial data. The system can also differentiate its use between the owner and the employee. It is useful for ensuring the confidentiality and protection of company revenue and expenditure data.